Удмурт-ӟуч, ӟуч-удмурт кыллюкам: ог 6500 пала кыл / [редакторы-составители Т. В. Воронова, Т. А. Пояркова] - Воронова Т. В. (Удмуртия, 2015)
Экземпляры: (20170904) / Инвентарный номер: 49690 / Цена: 200.00 / Сис.шифр: 81.2(2РусУдм) / Авт.знак: У 30 / ГРНТИ: 16 / ББК: 81.2(2РусУдм)